2008
DOI: 10.1016/j.bios.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of continuous magnetic field on the separation of ephedrine enantiomers by molecularly imprinted polymers

Abstract: A set of polymers was imprinted with (-)-ephedrine using UV initiation, under the influence of a constant external magnetic field with intensities ranging from 0 to 1.55 T. Synthesised materials were characterised by X-ray crystallography, infrared spectroscopy, swelling and surface area. Recognition properties were assessed by the ability to discriminate between (+) and (-)-ephedrine and by Scatchard analyses on chromatographic mode. It was shown that polymer morphology and recognition properties are affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In considering the XRD spectra of the samples, it can be stated that the spherulitic morphology exhibits the crystallinity of the sample 1MF. It was found that the polymers synthesized under MF are more rigid and ordered structure in the literature [27]. EDX mapping images were given to reveal the distribution of N, O and S atoms in the composites.…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In considering the XRD spectra of the samples, it can be stated that the spherulitic morphology exhibits the crystallinity of the sample 1MF. It was found that the polymers synthesized under MF are more rigid and ordered structure in the literature [27]. EDX mapping images were given to reveal the distribution of N, O and S atoms in the composites.…”
Section: Xrd Analysismentioning
confidence: 99%
“…It was reported that the polymers synthesized in an external MF demonstrate increased thermal stability and lower swelling due to their regulated structures. It was found that imprinted polymers synthesized under MF were more rigid and ordered [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MIPs are also used for many purposes such as adsorption of 17␤-estradiol (Wei and Mizaikoff, 2007), reflectometric interference spectroscopic sensing of atrazine (Belmont et al, 2007), separation of ephedrine enantiomers (Guerreiro et al, 2008), hanging mercury drop MIP modified electrode for differential pulse cathodic stripping voltammetric analysis of creatine (Lakshmi et al, 2007), fructosyl valine recognition (Rajkumar et al, 2007), solid phase extraction of photosynthesisinhibiting herbicides (Breton et al, 2007), biorecognition solvent extraction agents (Castell et al, 2006), recognition of atrazine (Lavignac et al, 2006), fabrication of bilirubin-specific sensor (Huang et al, 2007), adsorption study of dansylated amino acids by surface plasmon resonance (Li and Husson, 2006), cholesterol recognition (Boonpangrak et al, 2006), recognition of copper (Baghel et al, 2007) recognition of chemical warfare agent sulfur mustard (Boopathi et al, 2006), recognition of ochratoxin A (Turner et al, 2004) and also in catalysing a trans esterification process (Meng et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ephedrine is widely used as an energizing-stimulating substance for athletes and in various diet foods for exciting central nervous system. Several studies concerning MIPs with ephedrine as the template molecule have been reported [21][22][23]. In those cases, the MIP was used as an LC stationary phase.…”
Section: Introductionmentioning
confidence: 99%